ZOOPLANKTON DIVERSITY AND ITS RELATIONSHIP WITH PHYSICO-CHEMICAL PARAMETERS IN MANI RESERVOIR OF WESTERN GHATS, INDIA - D. N. Veerendra; S. Thirumala; H. Manjunatha; H. B. Aravinda (Journal of Urban and Environmental Engineering, 2012)
Studies on relationship between zooplankton abundance and water quality parameter in Mani reservoir were made between January 2008 and December 2008.in the urrent investigation, impact of different physico-chemical parameters on zooplankton population was found. Ten genera of zooplankton were identified. The relationship between zooplankton and water quality parameters was varied from place to place depending upon the condition of the reservoir water.